Avaliação dos efeitos renais e vasculares do veneno da Bothrops insularis e de frações isoladas - Braga, Marcus Davis Machado (2006)
We investigated the biochemical and biological effects of the whole venom from Bothrops insularis (popularly known as “golden lancet”), and four of its fractions, a thrombin-like enzyme, a lectin-like substance, an L-amino acid oxidase and a phospholipase A2, in perfused rat kidneys and vascular sistem. The fractions were purified by a combination of Sephadex gel filtration in HPLC columns, and ion-exchange chromatography on DEAE-Sephadex in reverse phase, low-pressure affinity columns. We used a modified isolated perfused rat kidney assay, with Krebs-Henseleit solution as the perfusion fluid (Bowman, 1970; Fonteles et al., 1998). Selected parameters of renal function during stable experimental conditions were evaluated before and at 60, 90, and 120 minutes after infusion of venom and its fractions, with the first 30 minutes interval constituting the paired control. In the systemic vascular bed (Ferreira, 1965), the arterial pressure was evaluated by a manometer connected through a canule to carotid common artery and the venom was injected into the jugular vein, with registers made at every 10 minutes after administration in increasing doses, until an infusion of 300mcg was reached at 60 minutes. In the isolated rat mesenteric blood vessels method (McGregor, 1965), the perfusions were done with Krebs-Henseleit solution, at a constant flow rate of 4mL/minute. The perfusion pressure was measured manometrically. Statistical evaluations were performed by analysis of variance (ANOVA) and Bonferroni test, at the 5% significance level. In perfused kidney studies, the group treated with the whole venom showed a fall in all physiological parameters, except in potassium transport. With the lectin-like fraction, the perfusion pressure rose initially, followed by a fall, along with urinary flow and glomerular filtration rate. Sodium and potassium tubular reabsorption increased, with a fall in the osmotic clearance. The thrombin-like fraction promoted an initial rise followed by a fall in the end, in almost all parameters except in the renal vascular resistance. The sodium and chloride tubular reabsorption fell. There was an initial rise in the potassium transport, and an initial rise followed by a fall in the osmotic clearance. With the L-amino acid oxidase fraction, there was a fall in all the parameters studied. The Phospholipase A2 fraction induced a rise in the physiological and vascular parameters, as also in the potassium transport and osmotic clearance; accompanied by a fall in sodium and chloride reabsorption. With the exception of the thrombin-like fraction, all the substances tested induced acute tubular necrosis in perfused kidneys in the end. Protein extravasation into the Bowman space was evidenced in all perfused kidneys except in those treated with the whole venom; but was more intense with the thrombin-like fraction. In the systemic arterial bed, the whole venom raised arterial pressure in a dose-dependant manner, except at the concentration of 10mcg; in addition to causing intense pulmonary hemorrhage with neutrophils and alveolar lymphocyte proliferation, renal hemorrhage, and generalized vascular dilatation and congestion. In the isolated mesenteric artery, there was a marked fall in perfusion pressure when the whole venom was infused into the vessel pre-contracted with phenillephrine, as also in the isolated vessel without phenillephrine. We conclude that Bothrops insularis venom shows vasodilatation and hemorrhagic potential, like other venoms of the genus; but, different from other Bothrops venoms, it also reveals a significant necrotic activity when perfused into isolated rat kidney, causing acute tubular necrosis.